2010
DOI: 10.1089/end.2009.0210
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Renal Access: The Learning Curve of a Simplified Approach

Abstract: The fluoroscopy-guided approach used in this study is an effective and reproducible technique. Our analysis revealed that at least 50 procedures are needed to acquire reliable competence in obtaining access to the kidney.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 11 publications
1
7
0
1
Order By: Relevance
“…A total of six studies evaluated the learning curve for PCNL and renal access (Table ). In addition to total OT, complications and LOS the variables measured included stone extraction rate, stone‐free rate (SFR) and fluoroscopy time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of six studies evaluated the learning curve for PCNL and renal access (Table ). In addition to total OT, complications and LOS the variables measured included stone extraction rate, stone‐free rate (SFR) and fluoroscopy time.…”
Section: Resultsmentioning
confidence: 99%
“…A similar study by Negrete‐Pulido et al. reviewed 92 percutaneous renal accesses in patients with renal stones or PUJ obstruction performed by an endourology fellow without previous experience in percutaneous surgery. The rate of success increased from 82.5 to 97.6% after the first 40 punctures.…”
Section: Resultsmentioning
confidence: 99%
“…Similar results were reported by Tanriverdi et al [44], who found that approximately 60 procedures are necessary for a non-experienced urologist to gain competence in FGA PCNL, as after this amount there was no significant drop in operating time or radiation exposure. More recent data suggest that at least 50 procedures of FGA PCNL are necessary in order to achieve reliable skills in accessing the collecting system [45].…”
Section: Resultsmentioning
confidence: 99%
“…Many studies defined the learning curve for PCNL, jointly suggesting that at least 50 to 60 procedures are needed to acquire reliable competence in obtaining access to the kidney and a success rate between 82.5% and 97.6%. 4,5 Although salvage PCNL data on its safety and cogency, after previous unsuccessful PCNL, are available, 2 this is not yet for salvage ECIRS although its effectiveness has already been demonstrated as primary procedure. 6,7 We wanted to provide ECIRS feasibility in a salvage setting after previous failed PCNL.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%